âPENGARUH HUTANG, PROFITABILITAS, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN DAN KONSEKUENSINYA TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTURâ - Fitria Ismawati Dewi, 14.05.51.0135; Taswan, Taswan (Students Journal of Economic and Management, 2018)
This study aimed to examines the influence of the debt, profitability, liquidity, and firm size on dividend policy and its consequences to firm value. This research was conducted at Indonesia by using analysis unit manufacturing company that have gone public. The population of this research is manufacturing company that listed in Indonesia Stock Exchange. The sampling method using purposive sampling with the study period of 2014 until 2016 and obtained as many as 85 companies. The technique of data analysis is used multiple regression analysis with documentation method. The results of this study shows that debt and liquidity negatively insignificant affect dividend policy. Profitability and firm size have a significant positive effect on dividend policy. While dividend policy has significant positive effect on firm value.Keyword: Debt, profitability, liquidity, firm size, dividend policy and firm value